If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3 + -1n) + 6n = -5n + 3(3n + -8) (3 * -7 + -1n * -7) + 6n = -5n + 3(3n + -8) (-21 + 7n) + 6n = -5n + 3(3n + -8) Combine like terms: 7n + 6n = 13n -21 + 13n = -5n + 3(3n + -8) Reorder the terms: -21 + 13n = -5n + 3(-8 + 3n) -21 + 13n = -5n + (-8 * 3 + 3n * 3) -21 + 13n = -5n + (-24 + 9n) Reorder the terms: -21 + 13n = -24 + -5n + 9n Combine like terms: -5n + 9n = 4n -21 + 13n = -24 + 4n Solving -21 + 13n = -24 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -21 + 13n + -4n = -24 + 4n + -4n Combine like terms: 13n + -4n = 9n -21 + 9n = -24 + 4n + -4n Combine like terms: 4n + -4n = 0 -21 + 9n = -24 + 0 -21 + 9n = -24 Add '21' to each side of the equation. -21 + 21 + 9n = -24 + 21 Combine like terms: -21 + 21 = 0 0 + 9n = -24 + 21 9n = -24 + 21 Combine like terms: -24 + 21 = -3 9n = -3 Divide each side by '9'. n = -0.3333333333 Simplifying n = -0.3333333333
| 100n-1500=9 | | -250x-75x^2+25x^3=0 | | 5y+38=17y-4 | | 12x^6-15x^3+4x^4-5x=0 | | -2(x-4)-(3x-2)=2-(6x-2) | | (7y+6)-(3+6y)=9 | | -7(r+10)=-49 | | 2(3x-1)=2(3x+1)-2x | | -2x-4x+6x=8-3-6+1 | | y-6=5x | | 15m^2-14m+3=0 | | 13x+11y-3x+3y+9= | | 4q-35=5 | | 3x-9x+30=15-2x-4 | | 3a-4=10 | | -1-(-x)=3x-5 | | 4y-9-6y=2(y+5)-3 | | 75-t^2=0 | | (y-7)-(y-7)=9y | | .30(80)+.60x=.40 | | 6(h+4)=-3 | | -2/1.1=x | | 3(5x-3)=4(2x+1)-6x | | -[-23-44+(-15)]+(-10)= | | -4x-4(6x-4)=-164 | | 19x-29y=13 | | 2x+2(x+3)=24 | | E=I(R+N) | | 65x^2+1=14x | | x^2+5x-472=0 | | 11x/10=x-2 | | 11y=24x-23 |